TOR promotes guard cell starch degradation by regulating the activity of β-AMYLASE1 in Arabidopsis. Issue 3 (17th December 2021) - Han, Chao; Hua, Wenbo; Li, Jinge; Qiao, Yan; Yao, Lianmei; Hao, Wei; Li, Ruizi; Fan, Min; De Jaeger, Geert; Yang, Wenqiang; Bai, Ming-Yi
Abstract: Starch is the main energy storage carbohydrate in plants and serves as an essential carbon storage molecule for plant metabolism and growth under changing environmental conditions. The TARGET of RAPAMYCIN (TOR) kinase is an evolutionarily conserved master regulator that integrates energy, nutrient, hormone, and stress signaling to regulate growth in all eukaryotes. Here, we demonstrate that TOR promotes guard cell starch degradation and induces stomatal opening in Arabidopsis thaliana . Starvation caused by plants growing under short photoperiod or low light photon irradiance, as well as inactivation of TOR, impaired guard cell starch degradation and stomatal opening. Sugar and TOR induce the accumulation of β-AMYLASE1 (BAM1), which is responsible for starch degradation in guard cells. The plant steroid hormone brassinosteroid and transcription factor BRASSINAZOLE-RESISTANT1 play crucial roles in sugar-promoted expression of BAM1 . Furthermore, sugar supply induced BAM1 accumulation, but TOR inactivation led to BAM1 degradation, and the effects of TOR inactivation on BAM1 degradation were abolished by the inhibition of autophagy and proteasome pathways or by phospho-mimicking mutation of BAM1 at serine-31. Such regulation of BAM1 activity by sugar–TOR signaling allows carbon availability to regulate guard cell starch metabolism and stomatal movement, ensuring optimal photosynthesis efficiency of plants. Abstract : TOR promotes BAM1 expression through BZR1, and induces BAM1 accumulation by inhibiting the autophagy and proteasome pathways, thereby promoting guard cell starch degradation and stomatal opening.